FEMALE STUDENTS PERCEPTION ON CHALLENGES AND OPPORTUNITIES FOR THEIR GENDER IN ENGINEERING TECHNOLOGY STUDIES AND THE PROFESSION - Alia Zahirah Zakaria; Muhammad Faiz Mohd Farrid; Muhammad Syadi Zakhwan Serkawi; Norkhairi Ahmad; Mohd Hanafia Huridi (Universitas Duta Bangsa Surakarta, 2025)
The field of engineering technology has been historically dominated by male students, resulting in a significant gender disparity in many countries. Female students pursuing engineering technology courses face unique challenges that can hinder their success and participation in the field. This research aims to explore the challenges faced by female students in engineering technology courses and present mitigating strategies to address the issues. A combination of basic quantitative survey was undertaken on a sampling of third year female students at a private engineering technology university. A qualitative interview was also conducted on a senior female academic staff who had extensive work experience in the field prior to become an academic. This served as a triangulation to the responses obtained from the surveyed respondents. Findings from the study shows that the challenges faced by the female students in engineering technology courses can be categorized into three main areas namely social and cultural barriers, academic obstacles, and lack of representation and support. As a whole, the female students have a positive perception on engineering technology as a tertiary study option and also as a career choice that they will continue to pursue. In addressing the challenges faced by female students in engineering technology courses, a multi-faceted approach is needed. The approach must also addressing social and cultural barriers and provide adequate academic support to empowers female students to thrive in engineering technology and contribute to the nation.